Optimization of Ultraviolet Sterilization Cabinet by Improving Light Reflection Using Aluminum Foil - Atika Hendryani; Wafa' Nabilah; Agus Komarudin (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
UV light radiation is the most important thing to sterilize medical devices. Over years studies continue to develop technology for sterilization using UV lights. This study aimed to develop an affordable UV cabinet sterilizer design by optimizing UV light using aluminum foil. The main contribution of this study is that the device can optimize the UV light intensity to whole over the cabinet. For instance, the device was only used two UV lamps as resources. Furthermore, the UV lights reflecting on the aluminum foil surface. To validate the results, the intensity of UV light was measured using a UV analyzer. The intensity was measured at 5 different points inside the device. This study has shown the measurement of UV light intensity at 5 different points were almost similar. The highest intensity was on center point 860 µW/cm^2, on the front area 632 µW/cm^2 and 606 µW/cm^2. On the rear area, the intensities are 630 µW/cm^2 and 670 µW/cm^2. This study improved the UV light intensity by using an aluminum surface to reflect the lights. This study has proven that UV radiation can be maximized by using the aluminum foil as the light reflector.